Analisis Keseimbangan Ekonomi Nasional ditinjau dari Tingkat Inflasi terhadap Inflation Targeting Framework, Suku Bunga dan Produk Domestik Bruto di Indonesia - Triana, Serli Ari; Moehadi, Moehadi (Ekonomis: Journal of Economics and Business, 2025)
This study analyzes the influence of monetary policy, especially the Inflation Targeting Framework (ITF), interest rates, and Gross Domestic Product (GDP) on inflation in Indonesia in the period 2005-2022. The aim is to understand how these three variables affect national economic stability, especially in maintaining inflation at a controlled level. This study uses secondary data from the World Bank and Bank Indonesia. The analysis method uses multiple regression analysis. The results of the analysis show that ITF, interest rates, and GDP significantly affect inflation in Indonesia